Attitudes towards mathematics: are girls and boys equal in their approach to learning? - Genoud, Philippe A.; Kappeler, Gabriel; Guillod, Matthias (Swiss Journal of Educational Research, 2018)
This article provides an analysis of socio-emotional attitudes of girls and boys concerning learning in mathematics during their post-compulsory education (high school). We were able to identify six typical profiles through a self-reported questionnaire assessing different perceptions students have in this discipline (perceived usefulness, perceived competence, controllability), their affect (positive, negative, and the feeling of being able to regulate) as well as the presence of the stereotype that math is associated to masculinity. These students are not only unequally distributed by gender but show differences in terms of investment. Such results question the impact of attitudes on motivation and student performance (including the vicious circles that are established), and especially on career guidance for teenagers about to enter universities and colleges.